Optical and luminescent properties of Dy3+/Sm3+ doped and codoped Zinc Borophosphate glasses for W-LED application - Dantas, N. F.; Melo, G. H.A.; Lodi, T. A. [UNESP]; Pedrochi, F.; Steimacher, A. (Elsevier, 2024)
In this work, a series of zinc borophosphate glasses (ZnPBAl), doped and codoped with Dy3+ and Sm3+, was studied for potential application in W-LEDs. The samples were prepared by the melt-quenching method and their luminescent and optical properties were investigated. The optical absorption spectra presented all Dy3+ and Sm3+ peaks corresponding to the transitions from the 6H15/2 and 6H5/2 states, respectively, to the excited energy levels. The 350 nm excitation source was chosen, considering photoluminescence excitation (PLE) results, to investigate the energy transfer from Dy3+ to Sm3+ ions. The energy transfer was indicated by photoluminescence (PL) spectra of Dy:Sm-codoped glasses and investigated by the energy transfer efficiency (η) using the lifetime data of both doped and codoped samples. The PL as a function of temperature was also studied. The CIE diagram of Dy-doped glasses showed their color emission close to the white region and the simulation of a combined Blue LED created an illumination route from warm to cold white light.
Keywords: Codoped glass; Dy3+; Sm3+; W-LED; ZnPBAl glass